Victimisation in a French population of children and youths with autism spectrum disorder: a case control study - A. Paul; C. Gallot; C. Lelouche; M. P. Bouvard; A. Amestoy (BMC, 2018)
Abstract Background Children and youths with autism spectrum disorder (ASD) have behavioural characteristics and severe social disabilities that make them vulnerable to victimisation. The current study explores the prevalence of peer victimisation in this population in France. Methods We used the Juvenile Victimization Questionnaire-Screener Sum Version in a French sample of 39 children and youths with ASD and 53 typically developing (TD) children and youths and tested the association of the victimisation with socio-demographic factors and clinical factors of anxiety and post-traumatic stress. Results The results indicate that 72% of the subjects with ASD had been victimised during the previous year and 94.9% during their entire lifetime. Of all students victimised at least once over the course of their lives, 75% had been victimised at school. Their peer victimisation score was significantly higher than in the TD group and was correlated to clinical factors such as a deficit in social skills and the severity of post-traumatic symptoms. Symptoms of anxiety were reported by parents of children and youths with ASD in 80% of cases. Conclusions Children and youths with ASD are particularly vulnerable to victimisation at school. Discussion focuses on the importance of considering the impacts and needs of school integration of this population in France in order to prevent these phenomena and their consequences.